2006
DOI: 10.1111/j.1365-2494.2006.00551.x
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of endophytes in grasses native to northern China

Abstract: A survey of grass species associated with Neotyphodium and Epichloë fungal endophytes was made in the permanent grasslands of northern China. A total of 41 grass species, 56 sites and 172 local populations were examined to reveal endophytic infection of native grasses. Twenty-five of the forty-one species of grasses (proportionately 0AE61) were infected by endophytes: twenty-two species had a mean infection rate of 0AE01-0AE50 and only three species had a mean infection >0AE50. Of the 172 local populations exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 18 publications
1
29
0
1
Order By: Relevance
“…It is usually a companion species in the grassland and sometimes can become a dominant species. High incidences of Neotyphodium endophyte infection (86-100%) in A. sibiricum were recorded in seven native populations in our previous study (Wei et al 2006). In this study, seeds of A. sibiricum were collected from natural populations in Hailar in Northeast China (119.67°E, 49.10°N).…”
Section: Study Systemmentioning
confidence: 95%
See 2 more Smart Citations
“…It is usually a companion species in the grassland and sometimes can become a dominant species. High incidences of Neotyphodium endophyte infection (86-100%) in A. sibiricum were recorded in seven native populations in our previous study (Wei et al 2006). In this study, seeds of A. sibiricum were collected from natural populations in Hailar in Northeast China (119.67°E, 49.10°N).…”
Section: Study Systemmentioning
confidence: 95%
“…After 5 years of continuous survey, Wei et al (2006) found that A. sibiricum is highly infected by Neotyphodium fungi, and there is little difference in infection rates among different geographic populations. Within the genus Achnatherum, there are five sections.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The endophyte in L. chinensis was first reported in Wei et al (2006), and was identified as Epichloë bromicola . E+ and E-grasses used in this research were originally collected from Abaga Banner of Inner Mongolia in 2010 and multiplied and selected for uniformity in 2011 and 2012.…”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%
“…The knowledge about these associations in arid environments is mostly restricted to reports of their natural occurrence and incidence in the populations (Wei et al, 2006;Rudgers et al, 2009;Iannone, 2010). However, very few studies have established the way in which the symbiosis outcome is regulated by genetic factors and ecological conditions (Novas et al, 2007;Wilson, 2007;Sullivan and Faeth, 2008;Iannone et al, 2013;Afkhami et al, 2014, Semmartín et al, 2014.…”
Section: Introductionmentioning
confidence: 98%